Peningkatan Produktivitas dan Pemasaran Produk Fermented Arabica Coffee di Rumah Kopi Banjarsengon Kecamatan Patrang Kabupaten Jember (Masyarakat Berkarya : Jurnal Pengabdian dan Perubahan Sosial, 2026)
The Community Partnership Program (PKM) at Rumah Kopi Banjarsengon (RKB) aims to improve product quality and coffee marketing according to consumer needs. Key activities include production observation, assistance with laboratory testing for nutritional value and shelf life, food safety education, digital marketing training, and the delivery of a 5 kg roasting machine. These efforts have successfully increased production capacity and product quality standards through informative labels. Digital marketing has seen significant progress, with increased social media engagement and broader market reach. Consumer satisfaction surveys have risen from 80 to 97 on a scale of 100. Overall, this PKM program not only supports sustainable coffee business development but also contributes to improving partner competency and strengthening product competitiveness in both local and export markets. RKB is expected to consistently implement digital marketing strategies and product innovation for long-term success. Going forward, RKB is expected to continue implementing digital marketing strategies and product innovation to ensure sustainable business success.